Melt-spun polypropylene filaments containing paraffin microcapsules for multifunctional hybrid yarns and smart thermoregulating thermoplastic composites - G. Fredi; H. Bruenig; R. Vogel; C. Scheffler (eXPRESS Polymer Letters)
The present work focuses on the development of polypropylene (PP) filaments containing paraffin microcapsules (MC), aimed at being incorporated in hybrid yarns to produce multifunctional thermoplastic laminates for thermal energy storage (TES). Benchmark experiments carried out on a small-scale melt compounder and piston-type melt spinning device resulted in the successful production of single filaments containing up to 30 wt% of MC, with diameters of 70–140 µm depending on the collection speed and a surface roughness that increases with the MC content. An increase in the MC fraction also determines a rise in the complex viscosity, but this effect is less evident at higher shear rates and likely almost negligible at the deformation rates typical of the spinning process. Although the MC have a considerable thermal stability, the compounded mixtures reported a sensible mass loss in isothermal thermogravimetric analysis (TGA) tests, which is linked to a not negligible MC damage during the compounding. Nevertheless, differential scanning calorimetry (DSC) on the spun filaments evidenced an increase in the phase change enthalpy with the MC content up to approx. 48 J/g, which is remarkably higher than that of similar systems reported in the literature. The elastic modulus and the properties at break decrease with an increase in the MC content, but the fiber strength is acceptable to produce a hybrid yarn and a thermoplastic laminate up to a MC fraction of 20 wt%.